The Relationship between Health-Related Quality of Life, Subjective Scar Estimation, and Activity Performance in Adult Burn Patients 6 and 12 Months after Injury - Sara Enblom; Elin Sundin; Gerd Edvinsson Guné; Nona Aspling; Fredrik Huss (MDPI AG, 2022)
A burn injury affects a person's health-related quality of life (HRQoL) in different ways and might influence their daily life for months and years afterward. The aim of this study was to examine how activity performance and subjective scar estimation relate to self-rated health and whether this changes in the first year post-burn. Fifty consecutive patients who were scheduled for follow-up at the Burn Center's outpatient clinic in Uppsala were included. Assessments of HRQoL (EQ-5D), activity performance (DASH), and subjective scar evaluation (POSAS) were conducted at 6 and 12 months post-burn. The results show a statistically significant correlation between self-rated HRQoL and activity performance (p = 0.001) and between self-rated HRQoL and subjective scar estimation (p = 0.000) at 6 but not at 12 months post-burn. A possible explanation of the lack of correlation at one year post-burn might be the patient´s expectations of his or her recovery. In future research, it would be interesting to investigate the long-term correlations between quality of life and activity performance.